Molecular, serological and biological characterization of a novel Apple stem pitting virus strain from a local pear variety grown in China - Liu LI; Meng-meng ZHENG; Xiao-fang MA; Yuan-jun LI; Qing-yu LI; Guo-ping WANG; Ni HONG (Journal of Integrative Agriculture, 2019)
Apple stem pitting virus (ASPV) is an important causal agent of pear diseases. Nowadays, the infection status and molecular characteristics of the virus in old pear trees have never been investigated. In this study, we provide the first complete genome sequence of an ASPV isolate LYC from an over 300-year-old tree of a local Pyrus bretschneideri cultivar ‘Chili’ specifically grown at Laiyang area in China. ASPV-LYC possesses a chimeric genome consisting of 9 273 nucleotides excluding a poly(A) tail at its 3’ end and harboring a recombination region in its open reading frame (ORF1) with Aurora-1 and KL9 identified as the major and minor parents. Western blot analysis with antisera against recombinant coat proteins (CPs) of three ASPV isolates from pear indicates that ASPV-LYC is serologically related to these ASPV isolates, but with differential activities. Further biological tests on indicator plants of Pyronia veitchii show that ASPV-LYC can induce serious leaf and stem symptoms as other ASPV isolates. The results provide an important information for understanding molecular evolution of ASPV and suggest a need to prevent dissemination of the isolate among pear trees.